The Effect of Tourist’ Motivation, Satisfaction, Loyalty in Kawasan Wisata Pendidikan Lingkungan Hidup (KWPLH) Balikpapan, East Borneo - Pratama Syarif, Febby Rio (Cerdika: Jurnal Ilmiah Indonesia, 2025)
KWPLH (Kawasan Wisata Pendidikan Lingkungan Hidup) is an environmental education tourism site located in Balikpapan, East Kalimantan, Indonesia. Despite its potential, limited studies have examined tourist behavior in this niche destination. This study aims to analyze the effect of intrinsic and extrinsic motivation on tourist satisfaction and loyalty, including mediation through satisfaction. Using a quantitative method, data were collected via questionnaires distributed to 100 tourists, selected through accidental sampling. Structural Equation Modeling (SEM) with SmartPLS was used to evaluate the relationship among variables. Findings reveal that intrinsic and extrinsic motivations significantly influence satisfaction; satisfaction significantly impacts loyalty. Intrinsic motivation also directly influences loyalty, while extrinsic motivation shows no significant direct effect on loyalty. However, both types of motivation significantly affect loyalty when mediated by satisfaction. These results align with the theory of consumer behavior, emphasizing pre-purchase (motivation), purchase (satisfaction), and post-purchase (loyalty) stages. The study provides practical implications for KWPLH management and local authorities to enhance tourist experience by focusing on emotional and educational elements, improving facilities, and promoting environmental awareness. Future research may explore tourists' willingness to pay as a post-purchase indicator of loyalty, particularly in conservation-focused destinations.